WEBINAR NATIONAL SPIRITUAL CARE PADA ERA PANDEMI COVID-19 BAGI PERAWAT DAN MAHASISWA KEPERAWATAN - Murtiningsih; Sri Rahayu; Melati Fajarini; Andriati Reny Harwati; Siti Awa Abu Bakar; Turiman; Anik Sugiyanti; Nedra Wati Zaly; Muzamil; Teti Rahmawati; Ratna Sari Dewi; Dwi Agustina; Eddy Rosfiati; Nadirahillah; Suwarni Asman; Lia Rosita; Ade Kurniawan; Iis Safitri; Reza Rahmat (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2023)
Patients suffering from Covid 19 will experience problems not only in the physical aspect but also psychologically, where the patient feels anxiety about the threat of death. Nursing care needs to be comprehensively bio-psycho-socio-spiritual, but not all nurses provide care from the spiritual aspect. Knowledge of patients and health workers about how to fulfill spiritual care needs still needs to be improved. Thus, there is a need for health information about the fulfillment of spiritual care in hospitals. Based on the problems experienced by Covid patients it is not only physical, so it is also necessary to provide spiritual nursing care to provide comprehensive nursing care. This activity aims to improve the knowledge and skills of nurses and nursing students in providing spiritual nursing care to patients. In this activity, lectures and discussions were held about virtual spiritual nursing care via Zoom and accompanied by demonstrations of examples of facilitating patient worship through videos created and uploaded on YouTube. This activity was carried out in collaboration between the STIKes Jayakarta institution, DPK PPNI STIKes Jayakarta, and DPD PPNI East Jakarta. This activity was attended by 354 participants with backgrounds from students, nurses, lecturers, and the general public from various provinces in Indonesia. The results of this community service activity were obtained after a lecture; participants had good knowledge about spiritual care during the COVID-19 pandemic, as much as 86.4%. ---  Pasien yang menderita Covid 19 akan mengalami masalah tidak hanya pada aspek fisik saja, tetapi juga mempengaruhi psikologis dimana pasien merasa cemas dengan ancaman kematian.  Asuhan keperawatan perlu diberikan secara komprehensif bio psiko sosio spiritual, akan tetapi belum semua perawat memberikan asuhan dari aspek spiritual. Pengetahuan pasien dan petugas kesehatan tentang cara pemenuhan kebutuhan spiritual care masih belum memadai. Sehingga, perlu adanya informasi kesehatan tentang pemenuhan spiritual care di rumah sakit. Berdasarkan permasalahan yang dialami pasien Covid tidak hanya fisik saja, sehingga perlu juga memberikan asuhan keperawatan spiritual agar asuhan keperawatan yang diberikan komprehensif. Kegiatan ini bertujuan meningkatkan pengetahuan dan keterampilan perawat dan mahasiswa keperawatan dalam memberikan asuhan keperawatan spiritual kepada pasien. Pada kegiatan ini dilakukan ceramah dan diskusi tentang asuhan keperawatan spiritual secara virtual melalui zoom dan disertai juga dengan demonstrasi contoh memfasilitasi ibadah pasien melalui video yang telah dibuat dan diunggah pada YouTube. Kegiatan ini terlaksana atas kerjasama antara institusi STIKes Jayakarta, DPK PPNI STIKes Jayakarta, dan DPD PPNI Jakarta Timur. Kegiatan ini diikuti oleh 354 orang peserta yang berlatar belakang mahasiswa, perawat, dosen, dan juga masyarakat umum dari berbagai provinsi di Indonesia. Hasil kegiatan pengabdian kepada masyarakat ini didapatkan setelah diberikan ceramah, peserta mempunyai pengetahuan yang baik tentang spiritual care selama pandemik COVID-19 sebanyak 86,4 %.